2020
DOI: 10.3389/fneur.2020.00355
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Radiation Therapy for Large and Giant Cavernous Sinus Hemangioma: A Retrospective Study

Abstract: Surgical resection has been traditionally used as a treatment for cavernous sinus hemangioma (CSH). However, this is usually difficult due to tumor vascularity and results in complications especially in large and giant CSH (volume >20 cm 3). Previous studies have reported that radiotherapy (RT) provides an alternative treatment modality for hemangiomas. However, the optimized dose and fractions which control CSH and also protect the cognitive function remain unclear. This study reports our experience in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…CyberKnife treatment [18][19][20] and radiotherapy 22,23 have both been reported to result in impressive tumor control and low side-effect incidence in treating large or giant CSHs, findings which also indicate the sensitivity of CSHs to radiation treatment. In comparison, the radiation dose of GKRS is distributed in layers, like an onion, which makes the radiation dose to the tumor center 2 times higher than the dose to the tumor margin.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…CyberKnife treatment [18][19][20] and radiotherapy 22,23 have both been reported to result in impressive tumor control and low side-effect incidence in treating large or giant CSHs, findings which also indicate the sensitivity of CSHs to radiation treatment. In comparison, the radiation dose of GKRS is distributed in layers, like an onion, which makes the radiation dose to the tumor center 2 times higher than the dose to the tumor margin.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to GKRS, the reported therapies for giant CSHs include microsurgical resection, [2][3][4][5]28 CyberKnife therapy, [18][19][20] and radiotherapy. 22,23 Li et al 2 retrospectively reviewed surgical results of 47 patients with large-volume CSHs and gross-total resection in 26 (55.3%) cases with average intraoperative blood loss of 650 ml (range 100-3500 ml), and found that increased tumor size was a risk factor for unfavorable outcomes. In this study, CSH patients previously treated with GKRS were not included, and adjunct radiotherapy was recommended for patients with incomplete resection of CSHs, and excellent results were achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Cavernous Sinus Hemangiomas (CSHs) are rare benign vascular tumors, accounting for less than 2% of all cavernous sinus lesions ( 24 , 25 ). In our case series, Case 3 demonstrated a sellar mass infiltrating the right cavernous sinus, partially encompassing the adjacent intracavernous internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 A recent report of the use of fractionated RT in large (20-40 cc) and giant (>40 cc) CSH, with a marginal dose of 50 Gy in 25 fractions, demonstrated a mean tumor reduction of 79.7% and symptomatic improvement in all patients within 12 months. 29 Yang et al demonstrated that a personalised approach to GKRS in CSH, reserving staged procedures for large tumors resulted in 91.5% tumor volume reduction with complications in 3.7% of patients across a spectrum of 19 large and 23 giant CSH. 22 CyberKnife radiosurgery delivered as 21 Gy in 3 fractions or 22 Gy in 4 fractions also appears to be effective in giant CSH, producing 88% mean tumor reduction with no radiation-induced complications.…”
Section: Accepted Manuscriptmentioning
confidence: 99%